Impaired Neovascularization and Reduced Capillary Supply in the Malignant vs. Non-malignant Course of Experimental Renovascular Hypertension - Hartner, Andrea; Jagusch, Lisa; Cordasic, Nada; Amann, Kerstin; Veelken, Roland; Jacobi, Johannes; Hilgers, Karl F. (Frontiers in Physiology, 2016)
Malignant hypertension develops in some cases of hypertension but not in others. We hypothesized that an impaired neovascularization and a reduced capillary supply characterizes the malignant course of experimental hypertension. Two-kidney, one-clip renovascular hypertension was induced in rats; controls (sham) were sham operated. To distinguish malignant hypertension from non-malignant hypertension, we considered two factors: weight loss, and the number of typical vascular lesions (onion skin lesions and fibrinoid necroses) per kidney section of the nonclipped kidney. Animals in the upper half for both criteria were defined as malignant hypertensives. After 5 weeks, mean arterial blood pressure was elevated to the same degree in malignant hypertension and non-malignant hypertension whereas plasma renin and aldosterone were significantly higher in malignant hypertensives. The expression of plasminogen activator inhibitor-1 was elevated (up to 14-fold) in non-malignant but significantly more increased (up to 36-fold) in malignant hypertensive rats, compared to sham. As a bioassay for neovascularization, the area of granulation tissue ingrowth in polyvinyl discs (implanted subcutaneously) was reduced in malignant hypertension compared to non-malignant hypertension and sham, while there was no difference between non-malignant hypertension and sham. The number of renal and left ventricular capillaries was significantly lower in malignant hypertension compared to non-malignant hypertension, as was the number of proliferating endothelial cells. We conclude that an impaired neovascularization and capillarization occurs in malignant renovascular hypertension but not in the non-malignant course of the disease despite comparable blood pressure levels. This might contribute to the unique vascular lesions and progressive target organ damage observed in malignant hypertension.